MEMAHAMI TEORI KONSTRUKSI SOSIAL PETER L. BERGER - Aimie Sulaiman (Society, 2016)
Peter Berger attempt to redefine the nature and role of the sociology of knowledge, the first attempt to define the notion of “reality” and “knowledge”. Social phenomena were found in the experience of community that a continuous process, lived in the society as a whole in all its aspects (cognitive, psychomotor, emotional and intuitive). In other words, the social reality is implied in social interaction, social expressed in various social actions such as communicating through language, working through forms of social organization. This kind of social reality found in intersubjective experience. Intersubjective concept refers to the structure dimenasi public consciousness to individual consciousness in a special group who were with each other and interact. Second, how to examine the experience intersubyektf so we can see their social construction of reality? in other words, this question also questioned how to prepare the sociological research that found the essence of society in social phenomena. Third, the choice of logic which one needs to be applied in an effort to understand the social reality that have characteristics such as pluralist, dynamic, in the process of continuous change that ? The logic of the social sciences are what need to be controlled so that it is relevant to the interpretation of the sociological structure of public awareness as well as the structure of the individual consciousnes.